New record of Hexanchus griseus in the northwestern Mediterranean Sea with insights into its biology and feeding ecology: predator or scavenger? - RUIZ-GARCÍA, DAVID; GARCÍA-SALINAS, PABLO; RAGA, JUAN ANTONIO; MOURA, ANDRÉ E.; DROMBY , MORGANE; BARRÍA, CLAUDIO (Mediterranean Marine Science, 2023)
On 15 March 2021, a male Hexanchus griseus was incidentally captured by a commercial bottom trawler at 550-730 m depth in the Gulf of Valencia (Spain). The specimen measured 251.8 cm in total length, weighed 86.2 kg and its reproductive system was fully developed, characterizing it as the smallest mature male bluntnose sixgill shark recorded in the Mediterranean Sea. The specimen hosted the ectoparasitic copepod Demoleus heptapus. Remains of a Stenella coeruleoalba calf were identified in its stomach content by applying molecular methods. The feeding behaviour of H. griseus as either actively preying on live cetaceans or as scavenging on carcasses is reviewed and discussed to better understand the species’ role in marine food webs.